Interactive-Invention Instructional Strategy and Secondary School Students’ Achievement in Selected Electromagnetic Concepts in Ibadan North Local Government Area (LGA), Nigeria - Edidiong , Enyeneokpon Ukoh (European Scientific Journal, ESJ, 2022)
Physics translates scientific discoveries to technology but students’ achievement in the subject has been observed to be below expectation at all levels of education in Nigeria. Electromagnetism aspect of physics is one of the areas in physics that has been reported to be very wide in coverage and abstract in nature, but students have difficulty understanding it. This paper focuses on determining the effect of interactive-invention instructional strategy on secondary school students’ achievement in electromagnetic concepts in Ibadan North LGA of Nigeria. Mixed methods research design was adopted for the study. Three senior secondary schools were randomly selected from Ibadan North LGA and also randomly assigned to the two treatment groups and control group. Intact classes from the selected schools were used and a total of 125 students participated in the study. The two treatment groups were taught using the interactive-invention instructional strategy with the electric motor/generator learning kits. Treatment group I participants worked individually while Treatment group II worked in groups of five. The control group were taught using the conventional lecture method. Physics Achievement Worksheets (PAW), Physics Students’ Attitude Questionnaire (PSAQ), and in-class discussion guide were the instruments used. The result of the study indicates a significant main effect of treatment on students’ academic achievement in the Experimental groups (F (2, 124) = 88.00; p<0.05, partial η2 = 0.61) and a significant main effect of students’ attitude on their academic achievement in the treatment groups (F(1, 124) = 5.80; p<0.05, partial η2 = 0.49). It was recommended that physics teachers should adopt interactive-invention instructional strategy in teaching electromagnetism concepts.